CHIQINDILARDAN FOYDALANIB KOMPOZIT MATERIALLARNING SEMENT TEJASH TEXNOLOGIYASI - Sultanov, M.J.; Kabulova, L.B.; Izbasarova, G.B. (SCIENCE and SOCIETY, 2022)
In the article there was studied the effect of samples containing crushed sodium silicate in the composition of the composite binder on the strength properties.
Keywords: portlandcement; addition; composite addition; strength; concrete